2019
DOI: 10.1108/meq-07-2018-0120
|View full text |Cite
|
Sign up to set email alerts
|

Noise and emission characterization of off-grid diesel-powered generators in Nigeria

Abstract: Purpose Nigeria, a prominent country in Sub-Sahara Africa, is plagued with a protracted, erratic and low power supply. The purpose of this paper is to present an experimental investigation of the noise levels and pollutants’ (CO, CO2 and particulate matter (PM2.5)) concentrations associated with the prevalent use of diesel-powered generators in the country. It is aimed to provide information on the level of gaseous, particulate and noise pollutants that are related to diesel-powered generators that could assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…For generators, different studies have been conducted (Giwa, 2019a;Giwa, 2019b;Oguntoke & Adeyemi, 2017), in which large variations are found across age, fuel and size (Rmax-Rmin>5*Rstd). Diesel generators emit more than gasoline generators, and a higher power output generally also leads to higher emissions.…”
Section: D Lvmentioning
confidence: 99%
“…For generators, different studies have been conducted (Giwa, 2019a;Giwa, 2019b;Oguntoke & Adeyemi, 2017), in which large variations are found across age, fuel and size (Rmax-Rmin>5*Rstd). Diesel generators emit more than gasoline generators, and a higher power output generally also leads to higher emissions.…”
Section: D Lvmentioning
confidence: 99%
“…While the overall contributions of SMEs to atmospheric loads of pollutants may be difficult to estimate because of their predominantly informal nature; the huge numbers suggest that their contributions will be significant and will also impact indoor environments considering that majority are used in close proximity with residential apartments. Reports from individual researchers showed that gasoline and diesel generators emissions may be above permissible limits depending on age and frequency of maintenance (Giwa et al, 2018). Recent study by Giwa et al (2019c) found out that average emission levels of CO 2 , CO and PM 2.5 from small gasoline generators could be as high as 710 AE 19.1 ppm, 83 AE 4.0 ppm and 83 AE 4.1 μg/m 3 respectively.…”
Section: Small and Medium Enterprises (Smes) And Completely Informal Sectorsmentioning
confidence: 99%
“…Ademola Sonibare et al (2014) analyzed the urban environmental risk caused by the noise from diesel generators, which helped to evaluate the noise level safe area around diesel power generation. Similarly, Giwa et al (2019) studied noise pollution and air pollutants caused by diesel generators in Nigeria, thereby raising public awareness of the health risks of diesel power generation. In general, previous research works have analyzed the risks in the electricity market, such as the risks faced by market participants, the risks caused by external factors, or health risks caused by fossil fuel power generation.…”
Section: Literature Reviewmentioning
confidence: 99%